1984
DOI: 10.1007/bf02027689
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation among populations of marine algae

Abstract: Most of the information for genetic differentiation among populations of marine algae is from studies on ecotypic variation. Physiological ecotypes have been described for individuals showing different responses to temperature and salinity conditions. Morphological ecotypes have also been found associated with areas differing in wave exposure or different intertidal positions. Little is known on how genetic variation is organized within and between populations of marine algae. The occurrence of ecotypic variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 48 publications
1
12
0
3
Order By: Relevance
“…The variation of biological characteristics within the Porphyra population may result from selection in significant difference in temperature, which means adaptive-genetic variety may occur. Research has indicated that differentiation among populations of marine algae can be the result of direct modification of the environmental temperature difference (Bolton 1983;Innes 1984). The differentiation may manifest as morphological, physiological, and biochemical differences (Innes 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The variation of biological characteristics within the Porphyra population may result from selection in significant difference in temperature, which means adaptive-genetic variety may occur. Research has indicated that differentiation among populations of marine algae can be the result of direct modification of the environmental temperature difference (Bolton 1983;Innes 1984). The differentiation may manifest as morphological, physiological, and biochemical differences (Innes 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The methodology employed in this paper might be particularly useful in indicating biochemical differentidtion in populations that are morphologically undifferentiated. Similarly, isozyme studies such as those discussed by Innes (1984) would be useful; however, it should be noted that there are considerable problems in giving phylogenetic interpretations to such data types (Farris, 1981).…”
Section: Vicariance Biogeographymentioning
confidence: 99%
“…That is, due to their morphological plasticity and interfertility, taxonomic delineations of several kelp species have been confusing (Chapman, 1974;Mathieson et al, 1980;Yarish et al, 1990). Recent interfertility studies have demonstrated that interspecific and possibly intergeneric hybridization may occur (Ltining et al, 1978;Mathieson et al, 1981;Bolton etal., 1983;Innes, 1984;Egan et al, 1989;Neushul, 1989). For example, Cosson & Olivari (1982) describe interspecific hybrids of Laminaria digitata with L. saccharina and L. ochroleuca and between each of these and Saccorhiza polyschides.…”
Section: Introductionmentioning
confidence: 99%
“…Blair etal. (1982), Innes (1984Innes ( , 1987, and Innes & Yarish (1984) investigated genetic variation between species of green algae, while Cheney and Babbel (1978) and Cheney & Mathieson (1979) examined species of red algae. Marsden etal.…”
Section: Introductionmentioning
confidence: 99%